MENTAL HEALTH CARE PATHWAY: INTERSECTORAL STRATEGIES FOR PROMOTING COMPREHENSIVENESS AND REDUCING HARM - Pacheco Eugênio, Aline; de Andrade Brandão, Miriam; D’Arc Vieira Couto Astolphi, Joana; Alcântara de Sousa, Camila; da Silva Izidoro, Jaqueline; Barbosa Oliveira, Moisés; Ximenes Oliveira , Silvia; Soares Torres Martins, Yaponira (Revista Gênero e Interdisciplinaridade, 2026)
This article analyzes the construction of mental health care pathways from the perspective of comprehensiveness and intersectorality, based on a qualitative narrative review. Drawing on studies that address territorial experiences, emancipatory practices, and cross-sectoral articulation, it discusses the progress, limits, and challenges in consolidating Brazil’s Psychosocial Care Network. Mental health care requires more than clinical interventions it demands qualified listening, interinstitutional agreements, collaborative practices, and recognition of the social determinants of mental suffering. The analysis shows that, despite promising initiatives and mechanisms such as CAPS and Primary Health Care, major obstacles persist, including network fragmentation, lack of integrated flows, professional turnover, and undervaluing of health promotion strategies. Territorialization stands out as a strategic tool for contextualized care planning. Ultimately, the study emphasizes the urgency of public policies that strengthen mental health promotion through participatory and intersectoral action.